The psychometric properties of Indonesian version of WHO quality of life 100 in tuberculosis patients - Sri Yulianti; Rohman Azzam; Fitrian Rayasari; Henny Dwi Susanti; Widia Astuti A W; Dadang Saadulloh; Ninik Yunitri (Jurnal Keperawatan Padjadjaran, 2024)
dad